As mulheres na autoria do crime de tráfico de drogas e a justiça restaurativa para a construção da cultura de paz - Aguiar, Taís do Amaral de (2024)
This dissertation aims to analyze whether restorative justice can play a leading role in reducing drug trafficking crimes committed by women, and how it can contribute to the creation of a culture of peace in society, based on a new perspective on crime, both for the offender and the victim. The discussion focuses on the penal system and criminology, with regard to drug trafficking, which is the crime that most often leads to women being imprisoned in Brazil. It also examines the current lack of legitimacy of the retributive system and the restorative model for dealing with the high rates of women in prison. In conclusion, the method used in the investigation was comparative deductive, examining the history of women facing the patriarchal system and crime, observing the practices and purposes of restorative justice, and comparing more recent data collected from Brazilian prison information systems. In the procedures, the choice was for a monographic format, in consultations with books, legislation and scientific articles that were related to the researched topics. In this context, it is pointed out that criminology, in gender relations, displays a patriarchal perception, stimulated by social culture, which places men as superior to women. The punitive system is a practice that goes beyond its function, being selective and unequal when it punishes, ignoring social, economic and cultural differences. Meetings, seminars and resolutions have, over the years, developed proposals on restorative justice procedures, presenting challenges and possibilities of redefining punitive measures in the face of illicit acts committed and harm caused, and this can extend to women convicted and imprisoned for drug trafficking crimes. The possibilities of applying restorative justice to reduce drug trafficking crimes committed by women are reparative and agreed actions that, when implemented, can culminate in a culture of peace in society.